2021
DOI: 10.1098/rsbl.2020.0808
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal city lighting elicits a macroscale response from an insect outbreak population

Abstract: Anthropogenic environmental change affects organisms by exposing them to enhanced sensory stimuli that can elicit novel behavioural responses. A pervasive feature of the built environment is artificial nocturnal lighting, and brightly lit urban areas can influence organism abundance, distribution and community structure within proximate landscapes. In some cases, the attractive or disorienting effect of artificial light at night can draw animals into highly unfavourable habitats, acting as a macroscale attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…ALAN also affected a diurnal endoparasitoid Venturia canescens (Hymenoptera: Ichneumonidae) that parasitises the larvae of the Pyralidae, by extending its activity level into the night (Gomes et al, 2021); females of V. canascens exposed to low level ALAN also demonstrated a transgenerational effect with increased development time and increased latency for feeding in their offspring. In a massive collective phototactic response, 45 million individuals of Trimerotropis pallidipennis (Orthoptera: Acrididae), that are usually diurnal, were attracted to city lights in Las Vegas, USA (Tielens et al, 2021) during one of the perennial population outbreaks. Consequently, phototaxis can have devastating effects on even diurnal insect populations by triggering inappropriate behavioural activity.…”
Section: Effect Of Alan On Diurnal Insectsmentioning
confidence: 99%
“…ALAN also affected a diurnal endoparasitoid Venturia canescens (Hymenoptera: Ichneumonidae) that parasitises the larvae of the Pyralidae, by extending its activity level into the night (Gomes et al, 2021); females of V. canascens exposed to low level ALAN also demonstrated a transgenerational effect with increased development time and increased latency for feeding in their offspring. In a massive collective phototactic response, 45 million individuals of Trimerotropis pallidipennis (Orthoptera: Acrididae), that are usually diurnal, were attracted to city lights in Las Vegas, USA (Tielens et al, 2021) during one of the perennial population outbreaks. Consequently, phototaxis can have devastating effects on even diurnal insect populations by triggering inappropriate behavioural activity.…”
Section: Effect Of Alan On Diurnal Insectsmentioning
confidence: 99%
“…Using a combination of ALAN data from VIIRS and radar‐derived measurements of aerial insect abundance, Tielens et al . (2021) quantified the nocturnal movements of grasshopper swarms into urban areas as a result of attraction to light. Satellite data has also been used to investigate the phenological effects of light pollution on tree budburst (ffrench‐Constant et al ., 2016), suggesting potential for similar applications with insect phenology.…”
Section: Light Pollutionmentioning
confidence: 99%
“…Weather radar data is already providing new insights into bird migration (Farnsworth et al ., 2016; Dokter et al ., 2018; Nilsson et al ., 2019), and early investigations suggest good potential for its application within entomology. In North America, for example, weather radar has been used successfully to determine the abundance, displacement speed and direction of migrating corn earworm moths ( Helicoverpa zea ) (Westbrook, Eyster & Wolf, 2014) around the Texas–Mexico border, and to investigate the movement of grasshopper swarms in response to urban light pollution (Tielens et al ., 2021). In Europe, the BioDAR project is currently developing a library of weather radar signatures for different insect functional groups and has a citizen science project using weather radar to investigate the nuptial flights of alate ants [see https://biodarproject.org/].…”
Section: Future Prospectsmentioning
confidence: 99%
“…Numerous proof‐of‐concept and observational studies have shown that Doppler WSRs, with and without dual‐polarization, can be used to observe birds and insects and have argued for the potential of WSRs to provide insights into ecology (e.g. Bachmann & Zrnić, 2007 ; Chapman et al., 2011 ; Chilson, Bridge, et al., 2012 ; Chilson, Frick, et al., 2012 ; Dokter et al., 2011 ; Drake, 1990 ; Gauthreaux et al., 2008 ; Gauthreaux & Belser, 1998 ; Gourley et al., 2007 ; Melnikov et al., 2014 ; Melnikov et al., 2015 ; Rennie et al., 2010 ; Russell & Wilson, 1997 ; Russell & Wilson, 2001 ; Stepanian et al., 2020 ; Tielens et al., 2021 ; Westbrook et al., 2014 ; Westbrook & Eyster, 2017 ; Wilson et al., 1994 ; Zrnic & Ryzhkov, 1998 ; among many others). However, despite over 70 years passing since the first description of animals on radar (Crawford, 1949 ; Lack & Varley, 1945 ), the widespread application of WSRs for routine monitoring of volant animals is still hampered by two key problems: (i) the useful identification or categorization of taxa (the ‘classification problem’), and (ii) the quantification of biomass and biodiversity (the ‘quantification problem’).…”
Section: Introductionmentioning
confidence: 99%